Kinetics Crystallization and Polymorphism of Cocoa Butter throughout the Spontaneous Fermentation Process - Efraín M. Castro-Alayo; Llisela Torrejón-Valqui; Marleni Medina-Mendoza; Ilse S. Cayo-Colca; Fiorella P. Cárdenas-Toro (Foods, 2022)
The spontaneous fermentation process of Criollo cocoa is studied for its importance in the development of chocolate aroma precursors. This research supports the importance of spontaneous fermentation, which was studied through the crystallization behavior and polymorphisms of cocoa butter (CB), the most abundant component of chocolate that is responsible for its quality physical properties. The k-means technique was used with the CB crystallization kinetics parameters to observe the division of the process during the first stage (day 0–3). The experimental crystallization time was 15.78 min and the second stage (day 4–7) was 17.88 min. The Avrami index (1.2–2.94) showed that the CB crystallizes in the form of a rod/needle/fiber or plate throughout the process. CB produced metastable crystals of polyforms <semantics><msubsup>β1′</msubsup></semantics> and <semantics><msubsup>β2′</msubsup></semantics>. Three days of fermentation are proposed to generate Criollo cocoa beans with acceptable CB crystallization times.